PELAYANAN PUBLIK BAGI PENYANDANG DISABILITAS DI KOTA PADANG - Fatmawanti, Besse; Gantika, Naldi (Universitas Ekasakti, 2019)
Research is important written in a journal is caused by several reasons: First , fulfillment of public services, especially for persons with disabilities, is an obligation and responsibility of the government in terms of fulfillment, both in the form of public services in the form of roads and sidewalks that are useful for the movement of persons with disabilities or for their mobility from one place to another, as well as supporting life supporters of disability. Article 2 of Law No. 39 of 1999 concerning Human Rights states that the Republic of Indonesia recognizes and upholds human rights and basic human freedoms as rights which naturally inherit to and are inseparable from humans, which must be protected, respected and enforced for the sake of increasing human dignity . Then it is also regulated that the right to protect, respect and uphold human rights is the government and in full in Article 71 of Law No. 39 of 1999 concerning Human Rights stated that